Circadian Changes of Dendritic Spine Geometry in Mouse Barrel Cortex - Jasinska, Malgorzata; Woznicka, Olga; Jasek-Gajda, Ewa; Lis, Grzegorz J.; Pyza, Elzbieta; Litwin, Jan A. (Frontiers in Neuroscience, 2020)
The circadian rhythmicity changes the density and shape of dendritic spines in mouse somatosensory barrel cortex, influencing their stability and maturation. In this study, we analyzed the main geometric parameters of dendritic spines reflecting the strength of synapses located on these spines under light/dark (12:12) and constant darkness conditions, in order to distinguish between endogenously regulated and light driven parameters. Using morphological analysis of serial electron micrographs as well as three-dimensional reconstructions, we found that the light induces elongation of single-synapse spine necks and increase in the diameter of double-synapse spine necks, increasing and decreasing the isolation of synapses from the parent dendrite, respectively. During the subjective night of constant darkness, we observed an enlargement of postsynaptic density area in inhibitory synapses and an increase in the number of polyribosomes inside double-synapse spines. The results show that both endogenous effect (circadian clock/locomotor activity) and light affect the morphological parameters of single- and double-synapse spines in the somatosensory cortex: light reduces the efficiency of excitatory synapses on single-synapse spines, increases the effect of synaptic transmission in double-synapse spines and additionally masks the endogenous clock driven enlargement of inhibitory synapses located on double-synapse spines. This indicates a special role of double-synapse spines and their inhibitory synapses in the regulation of synaptic transmission during both, circadian and diurnal cycles in the mouse somatosensory cortex.